Weather Shocks and Entrepreneurship - Churchill, Sefa Awaworyi; Munyanyi, Musharavati Ephraim; Trinh, Trong-Anh (My University, 2021)
Using household panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey and satellite re-analysis temperature and rainfall data, we present the first study to examine the impact of weather shocks on entrepreneurship. We measure temperature and rainfall shocks at the postcode level, and find that an increase in the number of days of extreme temperature and rainfall in the previous period is associated with a decline in the probability of self-employment in the next period. We examine health, cognitive functioning and economic activity as potential mechanisms through which weather shocks transmit to entrepreneurship. We find suggestive evidence that cognitive functioning is a mechanism through which temperature shocks transmit to entrepreneurship, while economic activity is a mechanism through which both temperature and rainfall shocks transmit to entrepreneurship.
Keywords: Housing, communities and neighbourhoods; Labour market